Narcissistic traits and compassion: Embracing oneself while devoiding others - Freund, Vanessa Lea; Peeters, Frenk; Meesters, Cor; Geschwind, Nicole; Lemmens, Lotte H. J. M.; Bernstein, David P.; Lobbestael, Jill (Frontiers in Psychology, 2022)
Grandiose narcissistic traits refer to exploitative and arrogant attitudes, while vulnerable narcissistic traits entail hypersensitivity to judgment and low self-esteem. Little is known about how individuals with narcissistic traits can improve their attitudes toward themselves and others. The current research puts self- and other compassion forward as possible targets to alleviate some of destructive patterns of narcissism. Generally, self-compassion (SC) has previously been associated with beneficial effects on psychological wellbeing, while other compassion (OC) is advantageous for interpersonal relationships. This study explored the relationship between narcissistic traits and the efficacy of experimental compassion inductions. Student and community participants (N = 230, Mage = 27.41, 65.2% female) completed grandiose and vulnerable narcissistic trait, SC and OC state questionnaires, and either an SC or OC induction. It was expected that individuals with higher narcissistic traits (particularly grandiose traits) would benefit from the inductions and show higher SC after but would have greater difficulty showing meaningful increases in OC (especially OC directed at the general population). The results indicated that individual differences in grandiose and vulnerable narcissistic traits are related to the magnitude of improvements following the inductions: the theorized lack of SC in individuals with vulnerable oversensitivity to judgment traits seems possible to be counteracted through different types of compassion exercises. Moreover, higher grandiose exploitativeness–entitlement and global vulnerable narcissistic traits related to less increases than others. However, directly inducing OC in individuals with these traits was linked to greater OC improvements than improvements after inducing SC. Overall, the present findings suggest that self-compassionate behavior can be improved in individuals with high oversensitivity and that other compassionate behavior could potentially be increased if, specifically, other compassion exercises are utilized when higher levels of certain narcissistic traits are present.